Pengaruh Brand Image dan Service Quality Terhadap Customer Loyalty pada UMKM Ayam Goreng Roker di Kota Malang - Anggita Al Fathina; Lina Budiarti; Rena Feri Wijayanti (Indo Publishing, 2025)
The increasingly intense competition in the culinary business in Malang City requires business actors to not only rely on product quality, but also build a strong brand image and optimal service quality in order to create customer loyalty. This study aims to analyze the influence of brand image and service quality on customer loyalty at the Ayam Goreng Roker MSME in Malang City. This is an explanatory study using a quantitative approach. The sample consisted of 100 respondents selected through purposive sampling. Data was collected via a questionnaire and analyzed using multiple linear regression with the assistance of SPSS. The results of the partial tests indicate that brand image and service quality have a positive and significant influence on customer loyalty. Simultaneous testing also confirmed that both variables together signifcantly influence customer loyalty. These findings emphasize that strengthening brand image and improving service quality are important strategies for retaining customers. The recommendations provided are to enhance interaction, promotion, and product quality consistency to build sustainable loyalty.